Myth in constructing contemporary Indian identity in popular Hindi film: The case of Ashutosh Gowariker - Valančiūnas, Deimantas (Acta Orientalia Vilnensia, 2008)
Vilnius UniversityThe present paper concentrates on particular mytho-religious symbolism and mythological structures used in two popular films by famous contemporary Indian film director Ashutosh Gowariker: Lagaan (2001) and Swades (2004). These films are significant in the history of Indian popular cinema not only for their complex problems related to the sensitive topics of anti-colonialism, nationalism and patriotism, but also for their widely used mytho-religious symbolism. My goal in this essay is to analyse these two films, identifying the mythological symbols and mythological structures used in the films, and to see how they organise the films’ narrative and how they are connected with the issues of anti-colonialism, Hindu nationalism, and the construction of (idealised) Indian identity. In this paper I argue that the usage of mythological and mytho-religious symbolism functions as a useful tool for the director to transfer ideas related to national identity, nationalism, and anti-colonialism to the viewer effectively, as well as to express a political and social critique of contemporary India and to construct the images of idealised Indian identity in response.